The hunger games. Catching fire - Lawrence, Francis; Beaufoy, Simon; Arndt, Michael D.; Kilik, Jon; Jacobsen, Nina; Lawrence, Jennifer, 1990-; Hutcherson, Josh; Hemsworth, Liam, 1990-; Harrelson, Woody; Banks, Elizabeth, 1974-; Kravitz, Lenny; Hoffman, Philip Seymour, 1967-2014; et al. (Santa Monica, California : Lionsgate, 2014)
Katniss Everdeen has returned home safe after winning the 74th Annual Hunger Games along with fellow tribute Peeta Mellark. Winning means that they must embark on a "Victor's Tour" of the districts. Along the way Katniss senses that a rebellion is simmering, but the Capitol is still very much in control as President Snow prepares the 75th Annual Hunger Games (The Quarter Quell); a competition that could change Panem forever.
Originally released as a motion picture in 2013.
Based on the novel "Catching fire" by Suzanne Collins.
Special features: Deleted scenes; audio commentaries.
Jennifer Lawrence, Josh Hutcherson, Liam Hemsworth, Woody Harrelson, Elizabeth Banks, Lenny Kravitz, Philip Seymour Hoffman, Jeffrey Wright, Stanley Tucci, Donald Sutherland.
MPAA rating: PG-13; for intense sequences of violence and action, some frightening images, thematic elements, a suggestive situation and language.
DVD, widescreen presentation; 5.1 Dolby digital, NTSC, region 1.
Keywords: Insurgency -- Drama; Survival -- Drama; Television programs -- Drama; Interpersonal relations -- Drama; Contests -- Drama; Dystopian plays; Girls -- Drama; Courage -- Drama; Action and adventure films; Feature films; Films for the hearing impaired